FlashCam: A high-performance camera for IACTs - Escañuela Nieves Clara; Barcelo Miquel; Bauer Christian; Bi Baiyang; Diebold Sebastian; Föhr Christian; Funk Stefan; Haist Fabian; Hermann German; Heß Bastian; Hinton Jim; Jung-Richardt Ira; et al. (EPJ Web of Conferences)
FlashCam is an advanced camera developed for Imaging Atmospheric Cherenkov Telescopes (IACTs), aiming to significantly enhance ground-based astronomical observations. FlashCam has delivered exceptional performance within the High Energy Stereoscopic System (H.E.S.S.) for over 5 years. Its design has been thoroughly studied using laboratory data as well as accurate simulations, all of which show good agreement between simulated and observed results. Minor adjustments are being made to the camera design in preparation for its integration with the Cherenkov Telescope Array Observatory (CTAO). Calibration is a critical aspect of any detector, and muons provide an effective means to calibrate the telescope’s full optical throughput. For FlashCam, a specialized muon detection method achieves over 95% efciency in identifying muons, with a low background acceptance.